Community stakeholders' perspectives on youth mental health in India: Problems, challenges and recommendations. Issue 3 (21st May 2020) - Dhandapani, Vijaya Raghavan; Chandrasekaran, Sangeetha; Singh, Saurabh; Sood, Mamta; Chadda, Rakesh K; Shah, Jai; Iyer, Srividya; Meyer, Caroline; Mohan, Mohapradeep; Birchwood, Max; Madan, Jason; Currie, Graeme; et al.
Abstract: Background: India has a large youth population whose mental health needs must be addressed. This includes promotion of positive mental health, with early detection and effective intervention for mental health disorders. Understanding the perspectives of community stakeholders working with youth is pivotal to this effort. Current study aimed to bring together a group of community stakeholders (eg, parents, teachers, policy makers) to understand their perspectives on youth mental health problems, challenges in provision of care, and to provide recommendations to address these concerns at national level. Materials and methods: The study was conducted across two sites in India: Chennai and New Delhi. Three group meetings were conducted involving 52 participants, including governmental, non‐governmental and community representatives working with youth. The proceedings were manually recorded, transcribed, and analyzed using thematic analysis method. Results: Many youth mental health problems were similar across the two sites. The commonest drivers of mental health problems were reported to be academic pressure, substance use and problematic internet/social media use. Stigma and lack of awareness were identified as the most important challenges acting as barriers to seeking mental health help by youth. Prioritizing youth mental health as a national programmes along with strong political will were the major recommendations suggested by the stakeholders. Conclusion: Initial findings suggest that prioritizing youth mental health programmes in India would be advantageous. Inclusive and collaborative approach, involving community stakeholders working with youth in providing services that promote mental health and early access to care will help in developing healthy young citizens.